Indefinitely Oscillating Functions-Part I - T. El Bouayachi; N. Yebari (International Journal of Mathematics And its Applications, 2016)
This article details a class of indefinitely oscillating functions in H^s(% R). It is a class of functions of the Sobolev space H^s(% R) which have for all m integer one primitive of the order m in the same space.